Barriers reported among patients with breast and cervical abnormalities in the patient navigation research program: impact on timely care - Katz, Mira L. (2014)
BACKGROUND: Patient navigation (PN) is a system-level strategy to decrease cancer mortality rates by reducing barriers to cancer care. Barriers to resolution among participants in the PN intervention arm with a breast or cervical abnormality in the Patient Navigation Research Program (PNRP) and navigators’ actions to address those barriers were examined. METHODS: Data were from seven institutions (2005 to 2010) included 1,995 breast and 1,194 cervical patients. A stratified Cox proportional hazards regression model was used to examine the effects of barriers on time to resolution of an abnormal screening test or clinical finding. FINDINGS: The range of unique barriers was 0 to 12 and 0 to 7 among participants with breast and cervical abnormalities, respectively. About two-thirds of breast and half of cervical participants had at least one barrier resulting in longer time to diagnostic resolution among breast (adjusted HR=0.744; p<0.001) and cervical (adjusted HR=0.792; p<0.001) participants. Patient-level and system-level barriers were most common. Frequent navigator actions were: making arrangements, scheduling appointments, referrals, and education. CONCLUSIONS: Having a barrier resulted in a delay in diagnostic resolution of an abnormal screening test or clinical finding. Health care systems can use these findings to improve existing PN programs or when developing new programs.